Large Eddy Simulation of the Influences of the Pilot-Stage Structure on the Flow Characteristics in a Centrally Staged High-Temperature-Rise Combustor - Ge Hu; Qiongyao Qin; Wu Jin; Jianzhong Li (Aerospace, 2022)
Centrally staged combustion technique is often used in the military high-temperature-rise combustor. The pilot-stage structure affects the flow characteristics in the centrally staged combustor, which further affects the performance of ignition, combustion, and emission of military aero-engines. In order to increase the flow capacity of the swirler, the swirler with a non-rotating channel structure was designed. In this work, the influences of the pilot-stage structure on the flow characteristics in the centrally staged high-temperature-rise combustor are investigated. The flow fields of combustors with different pilot-stage swirl numbers (0.44, 0.60, and 0.71) are analyzed by large eddy simulation (LES). The results demonstrate that the primary recirculation zone (PRZ) becomes gradually longer and wider as the pilot-stage swirl number increases. In the combustors with three different pilot-stage structures, the precessing vortex core (PVC) was formed near the shear layer at the outlet of the pilot stage. The PVC frequency decreased from 1670 Hz to 1425 Hz and 1400 Hz with the increase of the pilot-stage swirl number from 0.44 to 0.60 and 0.71, respectively, and the breakdown position of the PVC shifted forward. The proper orthogonal decomposition (POD) and dynamic mode decomposition (DMD) methods are used to analyze the dynamic flow fields. It was observed that the corresponding frequency of the main pulsation structure decreased, and the flow instability was aggravated with the increase of the pilot-stage swirl number. The results deepen the understanding of the influences of the pilot-stage structure on the flow characteristics in the centrally staged high-temperature-rise combustor.